Seroprevalence of human cysticercosis in Maputo, Mozambique - Vilhena, Manuela (2020)
We carried out a serosurvey for cysticercosis among people visiting the Central Hospital of Maputo, the capital of Mozambique, between January and June 1993. A standardized questionnaire was designed to obtain information on demographic, socioeconomic, environmental, and behavioral characteristics related to the transmission of the infection. Four hundred eighty-nine individuals were tested for anti-cysticercosis antibodies: 222 blood donors and patients from the Department of Orthopedics, 148 patients from the Department of Neurology, and 119 patients from the Department of Psychiatry. The overall positivity rate was 12.1% (59 of 489). Anti-cysticercus antibodies was detected in 14.9% of the blood donors and patients from the Department of Orthopedics, 11.5% of the patients from the Department of Neurology, and 7.6% of the patients from the Department of Psychiatry. Living in poor sanitary conditions seems to be an important factor related to human cysticercosis in Maputo, Mozambique.